DEFINITION OF PATIENTS GENETIC PREDISPOSITION TO INCREASED WEAR OF DENTAL HARD TISSUES - I.M. Tkachenko (Український стоматологічний альманах, 2018)
In literature the information about research issues that the morphology of the teeth mainly caused by hereditary factors and the process of dentinogenesis regulated by many genes is not found. In our view, the genetic defect level in laying the epithelial authority may be the main factors that determine genetic susceptibility of patients to high abrasion. Violation of the protein components further leads to a change in the conclusion mineral crystal lattice and thus to change or violation of the structure of enamel prisms. It is process we believe the main etiological factor of high abrasion. After the morphogenesis of dental hard tissue throughout life not updated their biocenose internal environment is maintained by the dental pulp, cellular cement, periodontal fibers and saliva. In the matrix of tooth enamel developing there are two types of proteases. Early enamelizyn protease (MMP-20), at the end of enamel formation protease kallikrein 4 (KLK4). Mutations in MMP20 and KLK4 which cause autosomal recessive imperfect of amelogenesis lead to clinical presentation of soft (for physical characteristics) porous enamel which is unable to withstand functional stress due to trace amounts of protein content.